Colorimetric fluoride detection in dimethyl sulfoxide using a heteroleptic ruthenium(ii) complex with amino and amide groups: X-ray crystallographic and spectroscopic analyses. Issue 39 (7th September 2022) - Toyama, Mari; Hasegawa, Tomoki; Nagao, Noriharu
Abstract : A bis-heteroleptic ruthenium(ii ) complex; [Ru(Hdpa)2 (H2 pia)]X2 (1 ·X2 ; X = Cl, OTf, or F; Hdpa = di-2-pyridylamine; H2 pia = 2-pycolinamide; OTf – = CF3 SO3 – ) was synthesized and spectroscopically and crystallographically characterized. Abstract : A bis-heteroleptic ruthenium(ii ) complex, [Ru(Hdpa)2 (H2 pia)]X2 (1 ·X2 ; X = Cl, OTf, or F; Hdpa = di-2-pyridylamine; H2 pia = 2-pycolinamide; OTf − = CF3 SO3 − ), was synthesized and spectroscopically and crystallographically characterized. The crystal structures of 1 ·Cl2 ·2.5H2 O and 1 ·F2 ·2EtOH revealed essentially identical geometries for the 1 2+ dication; however, the dihedral angle between the two pyridyl groups in the Hdpa ligands, which represented the degree of bending of the bent conformation, was affected by hydrogen-bonding interactions between the NH group and counterions. In 1 ·F2 ·2EtOH, one of the Hdpa ligands had an unusually smaller dihedral angle (15.8°) than the others (29.9°–35.0°). The two NH groups of each Hdpa ligand and the NH2 group of the H2 pia ligand in 1 2+ acted as receptors for F − anion recognition via hydrogen-bonding interactions in a dimethyl sulfoxide (DMSO) solution, and the reaction showed an unambiguous color change in the visible region. Upon the addition of tetra- n -butylammonium fluoride to the red DMSO solution of 1 ·(OTf)2 ·H2 O, the solution turned dark brown. 1 H NMR analysis and absorption spectroscopy of the reaction between 1 2+ and the added F − anions revealed that the F − anions did not distinguish between the two amino groups of Hdpa and the amide group of H2 pia, although they were in different environments in the DMSO solution. A tris-F-adduct with 1 2+, 1 ·F3 −, was formed when sufficient F − anions were present in the solution, despite the presence of four NH protons in 1 2+ . Time-dependent DFT calculations of 1 2+ and 1 ·F3 − were consistent with their absorption spectra.